Sastra anak media penumbuhan nasionalisme bagi siswa sekolah dasar - Anafiah, Siti (Trihayu: Jurnal Pendidikan Ke-SD-an, 2025)
The development of nationalism values ​​among elementary school students is a crucial aspect in character education. In childhood, children experience a period of self-identity formation, so it is important to apply an approach that is appropriate to their environment. Children's literature, as one type of literary work that is adapted to the characteristics and needs of children, has great potential in instilling national values ​​in a gentle and enjoyable way. This article aims to analyze the role of children's literature as a means of developing nationalism for elementary school students, both in terms of story content, characters, and the values ​​contained therein. Through literature studies and analysis of expert opinions, it was revealed that children's literature can shape nationalist attitudes such as love for the homeland, tolerance, and appreciation for cultural diversity. Children's literature can also be used in thematic learning in elementary schools as a means to strengthen the values ​​of Pancasila and national identity. Therefore, the integration of children's literature into the education process is a strategic step to create a young generation that has a nationalist character.